Integritas Birokrasi Garis Depan (Street Level Bureaucracy) Dalam Meningkatkan Kualitas Pelayanan Publik Di Kantor Desa, Desa Sarirogo, Kecamatan Sidoarjo, Kabupaten Sidoarjo, Jawa Timur - Nunki Bias Nirwani; Achludin Ibnu Rochim; Indah Murti (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
Public service is one way for the central government to facilitate the community in data collection. Good public services can be assessed based on the quality of employees or apparatus within the agency. To fulfill this, the central government made a policy where in each region it is mandatory to have a village office, this is to facilitate the central government in providing various information about population and various programs. The role of the village apparatus has an important role in the quality of public services, especially the frontline bureaucracy. The frontline bureaucracy is someone who works in the public service, where they interact directly with the community. This research analyzes the integration of the frontline bureaucracy (Street Level Bureaucracy) in improving the quality of pubic services at the Sarirogo village office. The results of this study highlight what integrity is carried out by the Sarirogo village apparatus, especially the frontline bureaucracy, in improving the quality of existing public services. The findings provide valuable insights for the Sarirogo village apparatus and the community in the integrity of the frontline bureaucracy in improving the quality of public services in the Sarirogo village office, Sidoarjo District, Sidoarjo Regency.